2022
DOI: 10.3390/land11070969
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatial Patterns and Socioeconomic Activities of Urbanized Rural Areas in Fujian Province, China

Abstract: Rural urbanization under China’s process of rapid urbanization entails significant rural transformation and is profoundly influencing sustainable development. However, little research has been undertaken on spatial patterns and socioeconomic activities. In this study, we defined urbanized rural areas as territories where the population size, economic output, and built-up land area are larger than in other rural and urban areas. Using large-scale and high-granularity spatial data, we delimited 255 urbanized rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The influence of the proliferation of these traditionally developed cities predicts a significant growth trend in the future [82]. Concurrently, most regions in Xiamen, Fuzhou, Quanzhou, Zhangzhou, and Putian in Fujian also exhibit an upward trend, demonstrating the pattern of urban cluster development [83]. Thus, for these cities showing a clear increasing trend, we predict a persistent advancement of the urbanization process.…”
Section: Spatiotemporal Variation Characteristics Of Nighttime Light ...mentioning
confidence: 71%
“…The influence of the proliferation of these traditionally developed cities predicts a significant growth trend in the future [82]. Concurrently, most regions in Xiamen, Fuzhou, Quanzhou, Zhangzhou, and Putian in Fujian also exhibit an upward trend, demonstrating the pattern of urban cluster development [83]. Thus, for these cities showing a clear increasing trend, we predict a persistent advancement of the urbanization process.…”
Section: Spatiotemporal Variation Characteristics Of Nighttime Light ...mentioning
confidence: 71%
“…The interest-tendencies model is used to classify the scenic water spots of the tourist city, and then a classification model for the scenic water spots is constructed. In order to ensure that the selected scenic water spots have the optimal spatial distribution, a spatial accessibility model for the scenic water spots in the tourist city is set up, and then the spatial accessibility intensity for each scenic spot is calculated [21][22][23][24][25][26]. Combining the classification of scenic water spots and the spatial accessibility intensities, scenic water spots that optimally match the tourists' interests, and have the strongest spatial accessibility intensities, can be recommended for tourists, and then the tourist spatial decision-making model is set up.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies that explicitly stated that spatial changes in the village could have a significant impact on changes in rural communities' lifestyles had not been conducted (Mutunga 2018). Previous research has shown that climate change (Ajani & van der Geest 2021), globalization, modernization, technology (Hidayah 2017, Babbage et al 2020, and urbanization are all influencing changes in rural communities' lifestyles (Guo et al 2022, Raj & Shekhar 2022.…”
Section: Introductionmentioning
confidence: 99%